2019
DOI: 10.1111/are.14280
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate molecule size affects the metabolic and digestive dynamics of jundiá (Rhamdia quelen)

Abstract: This experiment was conducted to study the effects of carbohydrates with different molecular sizes on growth performance, feed utilization and composition, activity of digestive enzymes, plasma and hepatic metabolites of jundiá (Rhamdia quelen). Triplicate groups of jundiá (4.08 ± 0.005 g) were stocked in 12 tanks with stocking density of 25 individuals per tank and fed for 40 days with four isonitrogenous diets (37%) and isocaloric diets (3,200 kcal/kg) containing fructose (FRU), sucrose (SUC), maltodextrin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
(42 reference statements)
1
5
0
Order By: Relevance
“…The jundiá juveniles in this study showed a higher DSI when consuming diets containing fructose. This observation also occurred in another study conducted when jundiá were fed with fructose (Corrêia et al, 2019). It is hypothesized that this monosaccharide is absorbed more quickly and thereby changes the osmotic balance of enterocytes, increasing water influx into the cell (Baldisserotto et al, 2007).…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…The jundiá juveniles in this study showed a higher DSI when consuming diets containing fructose. This observation also occurred in another study conducted when jundiá were fed with fructose (Corrêia et al, 2019). It is hypothesized that this monosaccharide is absorbed more quickly and thereby changes the osmotic balance of enterocytes, increasing water influx into the cell (Baldisserotto et al, 2007).…”
Section: Discussionsupporting
confidence: 69%
“…The fish exhibited heavier final weights, higher specific growth rates, higher protein deposition, and less fat deposition when using rice in the form of raw starch. Corrêia et al (2019) The jundiá juveniles in this study showed a higher DSI when consuming diets containing fructose. This observation also occurred in another study conducted when jundiá were fed with fructose (Corrêia et al, 2019).…”
Section: Cascs or Casfru Diets)mentioning
confidence: 52%
See 3 more Smart Citations